DIGITAL BUSINESS TRANFORMATION: THE ULTIMATE STRATEGY OF PT. PLN (PERSERO) IN BOOSTING BUSINESS PERFORMANCE AND AVOIDING FINANCIAL DISTRESS - Sazly, Syukron; Al Rasyid, Harun; Tri Indah K, Agus (Universitas Muhammadiyah Tangerang, 2024)
This study investigates the financial distress of PT PLN (Persero), Indonesia's state-owned electricity provider, from 2019 to 2023 using the Springate S-Score method. Despite implementing digital business transformation and human resource development initiatives to enhance operational efficiency and service quality, PLN faces ongoing financial challenges. These challenges stem from high debt levels incurred due to the company's ambitious 35,000 MW power expansion project, as well as persistent cash flow difficulties. The study analyzes key financial indicators such as the debt-to-equity ratio, cash flow issues, and operational inefficiencies, tracking the company's fluctuating financial health. The Springate S-Score results indicate significant financial distress in 2021, reflecting the peak of PLN's financial pressures. However, improvements are observed in 2022 and 2023, signaling a gradual recovery as a result of cost-cutting measures and strategic adjustments. Based on the findings, the study recommends that PLN focus on reducing capital expenditures, renegotiating debt terms, and enhancing financial management practices. These measures are designed to stabilize the company’s financial position and improve its long-term sustainability, particularly as the energy sector continues to evolve with increasing demands for efficiency and renewable energy solutions. This study further emphasizes the impact of PLN’s operational inefficiencies, which have compounded its financial difficulties. The company's reliance on external financing has increased its vulnerability to debt servicing pressures. Additionally, the fluctuating energy prices and challenges in maintaining consistent revenue streams have added to its financial strain. By addressing these core issues, PLN can improve its resilience and adapt to the evolving energy landscape, ensuring both financial stability and operational sustainability in the long term. The recommendations provided aim to balance the need for infrastructure development with financial prudence, positioning PLN for a more secure future.Keywords: Business Transformation ,Financial Distress, Bankruptcy